The effect of temperature on the measurement of diffusion coefficients and antioxidant activities of ascorbic acid found in guava juice using cyclic voltammetry - Ang, Kurt Bryan A. (Animo Repository, 2015)
Ascorbic acid is the most abundant antioxidant present in guava (Psidiumguajava L.). There had only been few studies concerning the determination of both the antioxidant activity and the diffusion coefficent of ascorbic acid in guava juice using cyclic voltammetry at varying temperatures. Thus, this study on the effect of temperature on the antioxidant activity and diffusion coefficent on ascorbic acid found in guava was determined using cyclic voltammetry. The temperature tested were at 15 C, 25 C, 36 C, and 45 C. Electrodies used in the experiment were glassy carbon as the working electrode, platinum wire as the counter electrode, and Ag/AgCI electrode as the reference electrode. The results showed that the peak currents of ascorbic acid in guava juice at 15 C, 2 C, 36 C, and 45 C were -0.5720, -0.5380, -0.5000, and -0.4760 uA, respectively. The antioxidant activity, in terms of concentration, at the said temperatures were found to be 0.3374, 0.3212, 0.3015, and 0.2899 mM, respectively. The diffusion coefficient of the ascorbic acid obtained using the Randles-Seveik equation at all given temperatures and the values were 2.1489 x10, 2.1711 x105, and 2.2250 x10 cm2/S, respectively. It is concluded that a higher temperature, ascorbic acid in guava juice has a higher diffusion coefficent but lower antioxidant activity.